Characterization of fluid flow using random walk dynamics (2011)
"There has been growing need to characterize the fluid flow through a simplified model such as random walk dynamics. The research work covered three distinct regions of fluid flow namely the laminar region the transition region and the turbulent region Appropriate flow charts and FORTRAN-90 source codes were developed to solve relevant fluid flow governing equations. Reynolds number was used as the control parameter to tune from laminar to turbulent flow while relevant solution was graphed using Microsoft Excel. The graph shows the distinct regions. The first region characterizes laminar region will) three straight-line segments. The second region is the transition region, which is in form of wavy line segments. The third region is the turbulent region in which higher wavy line segments are shown. The degree of waviness and number of wavy line segments increases from transition region to turbulent region. The result shows that fluid flow can be characterized through the use of random walk dynamics. "